Chapter 7 Medical practitioners as collectors and communicators of natural history in Ireland, 1680-1750 - Marples, Alice (Social Histories of Medicine, 2019)
This chapter argues for the significant role played by Irish-based medics as collectors and communicators of natural history in the period 1680-1750. It demonstrates that the relative isolation of practitioners in Ireland meant that their findings could sometimes be seen by those elsewhere as carrying greater weight and possessing greater novelty. Particular use is made of the correspondence of Sir Hans Sloane, president of the Royal Society, to demonstrate how processes of communication and collection could operate across large distances, especially between rural Ireland and London.